Effects of physical activities that induce moderate external loading on bone metabolism in male athletes - Maimoun, L.; Mariano-Goulart, D.; Couret, I.; Manetta, J.; Peruchon, E.; Micallef, J. P.; Verdier, R.; Rossi, M.; Leroux, J. L. (Journal of Sports Sciences, 2004)
Sports characterized by little or moderate weight bearing or impact have a low osteogenic effect. However, the action of such sports on bone turnover remains unclear. The objective of this study was to determine the effect on bone remodelling of physical activities that induce moderate external loading on the skeleton. Thirty-eight male athletes aged 18-39 years (cyclists, n = 11; swimmers, n = 13; triathletes, n = 14) and 10 age-matched sedentary controls aged 22-35 years participated in the study. The study combined measurement of bone mineral density by dual-energy X-ray absorptiometry and bone turnover assessment from specific biochemical markers: serum bone-specific alkaline phosphatase, osteocalcin, urinary type I collagen C-telopeptide and calcium. Compared with the controls and swimmers, adjusted bone mineral density was higher (P < 0.05) in triathletes at the total proximal femur and lower limbs. No differences in bone mineral density were found between cyclists, swimmers and controls. Compared with controls, osteocalcin was higher (P < 0.05) in triathletes and swimmers and urinary type I collagen C-telopeptide was higher in swimmers only. Serum bone-specific alkaline phosphatase was lower (P < 0.05) in cyclists than in all other groups. In conclusion, an osteogenic effect was found only in triathletes, mainly at bone sites under high mechanical stress. Bone turnover differed in athletes compared with controls, suggesting that bone turnover may be sport-practice dependent. Despite some encouraging observations, it was not possible to show that changes in the bone remodelling process were sport-discipline dependent.